Preparation and use method of biomass super-strong universal adhesive

By homogenizing the aminated cellulose and the aqueous oxidized tannin solution in the biomass structure-type adhesive, and then adding glycerol triglycidyl ether to form a stable crosslinking network, the problem that existing adhesives require pressurization and hot pressing to achieve a better bonding effect is solved, and the effect of high-performance bonding is achieved without pressurization.

CN119614148AActive Publication Date: 2025-03-14SOUTHWEST FORESTRY UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411847439.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-14
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The existing biomass structure-type adhesives require pressing and hot pressing to achieve a better bonding effect during use, and even if the heating time is extended, the better bonding effect cannot be achieved.

Method used

By homogenizing the aminated cellulose with the aqueous oxidized tannin solution and adding glycerol triglycidyl ether to form a stable crosslinking network, thereby enhancing the cohesion of the adhesive and achieving high-performance bonding to various substrates without pressurization.

Benefits of technology

It achieves high-performance bonding without pressurization at room temperature or heating conditions, has excellent glue performance, and has certain solvent resistance, which is suitable for commercial production and applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614148A_ABST
    Figure CN119614148A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and a use method of a biomass super-strong universal adhesive, and belongs to the technical field of adhesives. The preparation method comprises the following steps: taking aminated cellulose as a skeleton, grafting amino groups on the aminated cellulose, and carrying out Schiff base reaction on the amino groups and quinonyl of oxidized tannin to form imine bonds so as to form a stable cross-linked network; according to the present invention, the epoxy group in the glycerol triglycidyl ether further reacts with the amino group even the hydroxyl group, and the cohesion of the adhesive is synergistically enhanced through a series of covalent effects and non-covalent effects, such that the biomass super-strong universal adhesive capable of carrying out high-performance adhesion on a variety of substrates is obtained, and the adhesion can be achieved without pressurization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to a preparation and use method of a biomass super-strong universal adhesive. Background Art

[0002] Structural adhesives are widely used in aerospace, automotive, construction, electronics, machinery, rail transit and many other fields due to their high strength, high load-bearing capacity, impact resistance, corrosion resistance, and ease of coating and construction. However, the synthetic raw materials of existing structural adhesives in the market, such as epoxy resins, polyurethanes, and acrylates, are mostly derived from fossil resources and are non-renewable resources. With the improvement of people's environmental awareness and the requirements of government policies, the production cost and supply stability of traditional adhesives are facing challenges. The use of biomass resources can reduce dependence on fossil energy, reduce carbon emissions, and meet the requirements of sustainable development.

[0003] Cellulose is a natural polymer compound that can be decomposed and degraded by microorganisms in the natural environment. It will not cause long-term pollution and harm to the environment, and it is in line with the concept of sustainable development. It can be used to prepare biomass structural adhesives. For example, the existing patent CN114836149A discloses an amine-functionalized modified cellulose cross-linked network structure and its preparation method and application. The patent uses aminated cellulose and trimethylolpropane triglycidyl ether to prepare a green and environmentally friendly cellulose cross-linked network wood adhesive.

[0004] Tannic acid, also known as tannic acid, is a polyphenol compound that is widely found in various plants, such as the bark and fruit of trees such as oak and sumac. It can replace the common raw materials of artificial board adhesives such as phenol and resorcinol, and can be used in the preparation of biomass structural adhesives. For example, the existing patent CN115353850A discloses an environmentally friendly and water-resistant tannin-based wood adhesive and its preparation method, which is synthesized by graft copolymerization and deamination reaction using epoxidized tannin, triethylenetetramine and urea as the main raw materials.

[0005] However, the adhesives prepared by the above-mentioned prior art need to be hot-pressed under a certain pressure during use to achieve a good bonding effect. If the pressure is omitted, even if the heating time is extended, a good bonding effect cannot be achieved. Summary of the invention

[0006] In order to solve the above technical problems, the present invention proposes a preparation and use method of a biomass super strong universal adhesive.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a biomass super strong universal adhesive, comprising the following steps:

[0009] The aminated cellulose is dispersed in an oxidized tannin aqueous solution, and after homogenization, glycerol triglycidyl ether is added and stirred to obtain a viscous liquid and an aqueous phase, and the obtained viscous liquid is separated to obtain the biomass super-strong universal adhesive.

[0010] Preferably, the mass ratio of the aminated cellulose, the oxidized tannin aqueous solution and glycerol triglycidyl ether is 3:11:(3-5).

[0011] Preferably, the aminated cellulose is obtained by reacting microcrystalline cellulose and aminopropyltriethoxysilane.

[0012] Preferably, the oxidized tannin aqueous solution is obtained by reacting hydrogen peroxide with a tannin aqueous solution.

[0013] Preferably, the solid content of the oxidized tannin aqueous solution is 20-40%.

[0014] The present invention provides a biomass super strong universal adhesive prepared by the preparation method described in the above technical solution.

[0015] The present invention also provides a method for using the biomass super-strong universal adhesive described in the above technical solution, comprising the following steps: using the biomass super-strong universal adhesive to overlap different substrates, and curing at room temperature or heating to complete the bonding of different substrates.

[0016] Preferably, the room temperature curing time is 72 to 240 hours.

[0017] Preferably, the temperature of the heating curing is 60-120° C. and the time is 0.5-1 h.

[0018] Preferably, the substrate includes one or more of wood, bamboo, stainless steel, aluminum, iron, copper, glass, marble, artificial quartz, zirconium oxide, and cloth.

[0019] Compared with the prior art, the present invention has the following advantages and technical effects:

[0020] The present invention uses aminated cellulose as a skeleton, and the aminated cellulose is grafted with amino groups. The amino groups can react with the quinone groups of oxidized tannins to form imine bonds through Schiff base reaction, thereby forming a stable cross-linked network. Then, glycerol triglycidyl ether is added, and the epoxy groups in the glycerol triglycidyl ether further react with the amino groups and even the hydroxyl groups. Through a series of covalent and non-covalent effects, the cohesive force of the adhesive is synergistically enhanced, thereby obtaining a biomass super-strong universal adhesive that can perform high-performance bonding on a variety of substrates, and bonding can be achieved without pressurization. It is expected to achieve commercial production and sales and partially replace the existing synthetic resin adhesives on the market. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0022] Figure 1 This is a reaction process diagram of preparing aminated cellulose from microcrystalline cellulose and APTES in step (1) of Example 1 of the present invention;

[0023] Figure 2 This is a reaction process diagram of preparing oxidized tannin from tannin and hydrogen peroxide in step (2) of Example 1 of the present invention;

[0024] Figure 3 is the structural formula of glycerol triglycidyl ether in step (3) of Example 1 of the present invention;

[0025] Figure 4 This is a schematic diagram of the structure of the biomass super strong multi-purpose adhesive prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0028] The embodiment of the present invention provides a method for preparing a biomass super strong universal adhesive, comprising the following steps:

[0029] Aminated cellulose (AC) is dispersed in an oxidized tannin (OTA) aqueous solution, and glycerol triglycidyl ether (GTE) is added after homogenization, and stirred to obtain a viscous liquid and an aqueous phase, and the obtained viscous liquid is separated to obtain the biomass super strong universal adhesive (ATG adhesive).

[0030] The present invention uses aminated cellulose as a skeleton, and the aminated cellulose is grafted with amino groups. The amino groups can react with the quinone groups of oxidized tannins to form imine bonds through Schiff base reaction, thereby forming a stable cross-linked network. Then, glycerol triglycidyl ether is added, and the epoxy groups in the glycerol triglycidyl ether further react with the amino groups and even the hydroxyl groups. Through a series of covalent and non-covalent effects, the cohesive force of the adhesive is synergistically enhanced, thereby obtaining a biomass super-strong universal adhesive that can perform high-performance bonding on a variety of substrates, and bonding can be achieved without pressurization. It is expected to achieve commercial production and sales and partially replace the existing synthetic resin adhesives on the market.

[0031] In a preferred embodiment, the mass ratio of the aminated cellulose, the oxidized tannin aqueous solution and glycerol triglycidyl ether is 3:11:(3-5). Since the molecular structure of the aminated cellulose is grafted with amino groups and the oxidized tannin has quinone groups, the aminated cellulose and the oxidized tannin are cross-linked by Schiff base reaction, and the glycerol triglycidyl ether is added to the cross-linked network by the reaction of epoxy groups with amino groups or hydroxyls. Therefore, the ratio of the three raw materials will affect the number of corresponding groups, thereby affecting the degree of reaction. The present invention controls the mass ratio of aminated cellulose, the oxidized tannin aqueous solution and glycerol triglycidyl ether within the above range, and the obtained biomass super strong universal adhesive has the best state and the best bonding performance. Changing the mass ratio of the three will make the bonding performance of the adhesive worse.

[0032] In a preferred embodiment, the aminated cellulose is obtained by reacting microcrystalline cellulose and aminopropyltriethoxysilane (APTES); wherein the reaction principle of microcrystalline cellulose and aminopropyltriethoxysilane is shown in Figure 1 .

[0033] The amount ratio of microcrystalline cellulose and aminopropyl triethoxysilane determines the degree of amino grafting. The more aminopropyl triethoxysilane is used, the more amino groups are grafted on the microcrystalline cellulose, which is more conducive to the subsequent cross-linking polymerization with oxidized tannins and glycerol triglycidyl ether. The inventors have experimentally verified that when the mass ratio of microcrystalline cellulose and aminopropyl triethoxysilane is 20:18, the maximum amino grafting amount can be guaranteed. Therefore, in a preferred embodiment, the mass ratio of microcrystalline cellulose and aminopropyl triethoxysilane is 20:18.

[0034] In a preferred embodiment, the preparation method of the aminated cellulose is as follows: microcrystalline cellulose and aminopropyltriethoxysilane are dispersed in water, stirred for reaction, filtered, washed and dried to obtain the aminated cellulose.

[0035] In a preferred embodiment, the mass ratio of microcrystalline cellulose, aminopropyltriethoxysilane and water is 20:18:100; the stirring reaction temperature is room temperature and the time is 24 hours; the washing reagent is deionized water; the drying temperature is 80°C and the equipment is an oven.

[0036] In a preferred embodiment, the oxidized tannin aqueous solution is obtained by reacting hydrogen peroxide with a tannin aqueous solution; wherein the reaction principle of hydrogen peroxide and tannin is shown in Figure 2 .

[0037] In a preferred embodiment, the mass ratio of hydrogen peroxide to tannin in the tannin aqueous solution is 0.5:3.4.

[0038] In a preferred embodiment, the preparation method of the oxidized tannin aqueous solution is specifically: dispersing tannin in water, then adding hydrogen peroxide, and stirring to obtain the oxidized tannin aqueous solution.

[0039] In a preferred embodiment, the mass ratio of hydrogen peroxide, tannin and water is 0.5:3.4:7.9; the stirring temperature is room temperature, and the stirring time is 10 minutes.

[0040] In a preferred embodiment, the solid content of the oxidized tannin aqueous solution is 20-40%. The solid content of the oxidized tannin aqueous solution in the present invention is within the above range, which is just enough to disperse the corresponding amount of aminated cellulose, without wasting water resources due to excessive water or causing poor dispersibility of the aminated cellulose due to insufficient water.

[0041] In a preferred embodiment, the homogenizing method is stirring.

[0042] The present invention provides a biomass super strong universal adhesive prepared by the preparation method described in the above technical solution.

[0043] The biomass super-strong universal adhesive provided by the invention has excellent gluing performance, can perform high-performance bonding on a variety of substrates, and can achieve bonding without applying pressure.

[0044] The present invention also provides a method for using the biomass super-strong universal adhesive described in the above technical solution, comprising the following steps: using the biomass super-strong universal adhesive to overlap different substrates, and curing at room temperature or heating to complete the bonding of different substrates.

[0045] In a preferred embodiment, the use of the biomass super-strong universal adhesive to overlap different substrates is specifically as follows: applying the biomass super-strong universal adhesive to one side of the surface of different substrates to form a bonding area, and then overlapping the bonding areas of the different substrates.

[0046] In a preferred embodiment, the substrate types of the different substrates may be the same or different.

[0047] In a preferred embodiment, the amount of the biomass super strong universal adhesive applied is 0.5 mm 2 / g.

[0048] In a preferred embodiment, the room temperature curing time is 72 to 240 hours; the room temperature curing does not require pressurization. The room temperature curing time is relatively long, but the water evaporates slowly, the adhesive layer is denser, and the energy consumption is less. As the curing time increases, the bonding performance shows an upward trend, which is suitable for long-term, energy-saving bonding.

[0049] In a preferred embodiment, the temperature of the heating curing is 60-120°C and the time is 0.5-1h; the heating curing does not require pressurization. The heating curing evaporates the water quickly, greatly shortens the curing time, effectively improves the use efficiency, and is suitable for rapid bonding.

[0050] In a preferred embodiment, the substrate includes one or more of wood, bamboo, stainless steel, aluminum, iron, copper, glass, marble, artificial quartz stone, zirconium oxide, and cloth.

[0051] The room temperature in the embodiments of the present invention refers to "25±3°C".

[0052] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.

[0053] In the following examples, the substrates used were purchased from the local market. The green and yellow colors of the bamboo were removed when purchased, and the surface of the metal substrate was polished smooth.

[0054] Glycerol triglycidyl ether is an industrial grade chemical purchased from Wuhan Smik Biotechnology Co., Ltd. The structural formula is shown in Figure 3 .

[0055] Example 1

[0056] A method for preparing a biomass super strong universal adhesive:

[0057] (1) 20 g of microcrystalline cellulose and 18 g of APTES were dispersed in 100 g of water, stirred at room temperature for 24 h, filtered, rinsed with deionized water, and then dried in an oven at 80 ° C to obtain aminated cellulose (AC);

[0058] (2) Disperse 3.4 g of tannin into 7.9 g of water, then add 0.5 g of hydrogen peroxide and stir at room temperature for 10 min to obtain an amber homogeneous transparent liquid, which is the oxidized tannin (OTA) aqueous solution;

[0059] (3) 3 g of AC obtained in step (1) was dispersed into 11 g of OTA aqueous solution with a solid content of 30% obtained in step (2), and after being stirred evenly at room temperature, 5 g of glycerol triglycidyl ether (GTE) was added, and stirring was continued at room temperature until a viscous liquid was formed to obtain a viscous liquid and an aqueous phase, and the obtained viscous liquid was separated to obtain a biomass super strong universal adhesive (ATG adhesive).

[0060] The reaction process of preparing aminated cellulose from microcrystalline cellulose and APTES in step (1) of Example 1 is shown in Figure 1 .

[0061] The reaction process of preparing oxidized tannin from tannin and hydrogen peroxide in step (2) of Example 1 is shown in Figure 2 .

[0062] The structural formula of glycerol triglycidyl ether in step (3) of Example 1 is shown in Figure 3 .

[0063] The structural diagram of the biomass super strong universal adhesive prepared in Example 1 is shown in Figure 4 .Depend on Figure 4 It can be seen that the biomass super strong universal adhesive prepared in Example 1 has a cross-linked network structure composed of aminated cellulose, oxidized tannin and glycerol triglycidyl ether.

[0064] Example 2

[0065] A method for using a biomass super strong universal adhesive:

[0066] The ATG adhesive prepared in Example 1 was 2 / g of coating amount was evenly applied on one side of the surface of two stainless steel substrates with a specification of 20mm×20mm to form a bonding area, and then the bonding areas of the two stainless steel substrates were overlapped and heated and cured at 120°C for 0.5h to complete the bonding of the substrates and obtain overlapping specimens.

[0067] Example 3

[0068] The difference from Example 2 is that the curing is carried out at room temperature for 72 hours, and the rest is the same as Example 2.

[0069] Example 4

[0070] The difference from Example 2 is that the curing is carried out at room temperature for 240 hours, and the other aspects are the same as Example 2.

[0071] Example 5

[0072] The difference from Example 2 is that the two stainless steel substrates are replaced by two wood substrates, and the rest is the same as Example 2.

[0073] Example 6

[0074] The difference from Example 2 is that the two stainless steel substrates are replaced by two pieces of glass, and the rest is the same as Example 2.

[0075] Example 7

[0076] The difference from Example 2 is that the two stainless steel substrates are replaced by two coppers, and the rest is the same as Example 2.

[0077] Example 8

[0078] The difference from Example 2 is that the two stainless steel substrates are replaced by two bamboo substrates, and the rest is the same as Example 2.

[0079] Comparative Example 1

[0080] A preparation method of TG adhesive:

[0081] (1) Disperse 3.4 g of tannin into 7.9 g of water, then add 0.5 g of hydrogen peroxide and stir at room temperature for 10 min to obtain an amber homogeneous transparent liquid, which is the oxidized tannin (OTA) aqueous solution;

[0082] (2) 5 g of glycerol triglycidyl ether (GTE) was added to 11 g of the OTA aqueous solution with a solid content of 30% obtained in step (1), and stirred at room temperature until a viscous liquid was formed to obtain a viscous liquid and an aqueous phase. The viscous liquid was separated to obtain a TG adhesive.

[0083] Comparative Examples 2-8

[0084] The difference from Example 2-8 is that the ATG adhesive prepared in Example 1 is replaced by the TG adhesive prepared in Comparative Example 1, and the other steps and parameters are the same as those of Example 2-8.

[0085] Comparative Example 9

[0086] A method for preparing AG adhesive:

[0087] (1) 20 g of microcrystalline cellulose and 18 g of APTES were dispersed in 100 g of water, stirred at room temperature for 24 h, filtered, rinsed with deionized water, and then dried in an oven at 80 ° C to obtain aminated cellulose (AC);

[0088] (2) 3 g of AC obtained in step (1) and 5 g of glycerol triglycidyl ether (GTE) were dispersed in water and stirred at room temperature until a viscous liquid was formed to obtain a viscous liquid and an aqueous phase. The viscous liquid was separated to obtain an AG adhesive.

[0089] Comparative Examples 10-16

[0090] The difference from Example 2-8 is that the ATG adhesive prepared in Example 1 is replaced by the AG adhesive prepared in Comparative Example 9, and the other steps and parameters are the same as those of Examples 2-8.

[0091] The lap shear strength of the lap specimens obtained in Examples 2-8, Comparative Examples 2-8 and Comparative Examples 10-16 were tested with reference to GB / T17657-2022 “Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels”. The results are shown in Table 1.

[0092] Table 1 Lap shear strength of lap joint specimens obtained from Examples 2-8, Comparative Examples 2-8 and Comparative Examples 10-16

[0093] Overlap test piece Lap shear strength (MPa) Example 2 37.11 Example 3 9.66 Example 4 13.28 Example 5 18.22 Example 6 25.21 Example 7 31.14 Example 8 22.71 Comparative Example 2 19.58 Comparative Example 3 0.89 Comparative Example 4 1.33 Comparative Example 5 15.92 Comparative Example 6 17.61 Comparative Example 7 15.85 Comparative Example 8 19.44 Comparative Example 10 / Comparative Example 11 / Comparative Example 12 / Comparative Example 13 1.26 Comparative Example 14 / Comparative Example 15 / Comparative Example 16 1.29

[0094] In the table, “ / ” means that the two substrates cannot be bonded.

[0095] The overlapped specimens obtained in Example 2 and Comparative Example 2 were immersed in water, dichloromethane and 0.1 mol / L hydrochloric acid for 30 days, respectively. The overlapped shear strength of the overlapped specimens was tested with reference to GB / T17657-2022 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels". The results are shown in Table 2.

[0096] Table 2 Lap shear strength of the lap joint specimens obtained in Example 2 and Comparative Example 2 after immersion in water, dichloromethane and 0.1 mol / L hydrochloric acid for 30 days

[0097] Lap shear strength (MPa) Example 2 water 14.70 Dichloromethane 12.03 0.1mol / L hydrochloric acid 8.75 Comparative Example 2 water / Dichloromethane / 0.1mol / L hydrochloric acid /

[0098] In the table, “ / ” means that after immersion for 30 days, the two substrates separated and the lap shear strength could not be tested.

[0099] As can be seen from Table 1, under room temperature conditions, as the curing time increases from 72h (Example 3) to 240h (Example 4), the bonding performance also increases, indicating that the curing time affects the bonding performance. Examples 5-8 explore the bonding performance of the ATG adhesive prepared in Example 1 to different substrates. It can be seen that the ATG adhesive can be bonded to different substrates. As can be seen from Table 2, the ATG adhesive prepared in Example 1 is tolerant to a variety of solvents, including organic solvents, inorganic solvents and strong acids, while the TG adhesive prepared in Comparative Example 1 is not tolerant to organic solvents, inorganic solvents and strong acids.

[0100] The influence of the adhesive components on the bonding performance is illustrated by comparing the examples with the comparative examples. The ATG adhesive prepared in Example 1 has multiple forces, thus generating a stronger cohesive force and excellent bonding performance; while the TG adhesive prepared in Comparative Example 1 has a single force, thus a relatively weak cohesive force and poor bonding performance.

[0101] In summary, the ATG adhesive provided by the present invention has the best bonding effect, can achieve bonding to a variety of substrates, and has a certain solvent resistance. In addition, under different requirements, a suitable curing temperature (room temperature or heating) and curing time can be selected.

[0102] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a biomass super strong universal adhesive, characterized in that: The following steps are involved: The aminated cellulose is dispersed in an oxidized tannin aqueous solution, and after homogenization, glycerol triglycidyl ether is added and stirred to obtain a viscous liquid and an aqueous phase, and the obtained viscous liquid is separated to obtain the biomass super-strong universal adhesive.

2. The method for preparing the biomass super strong universal adhesive according to claim 1, characterized in that: The mass ratio of the aminated cellulose, the oxidized tannin aqueous solution and glycerol triglycidyl ether is 3:11:(3-5).

3. The method for preparing the biomass super strong universal adhesive according to claim 1 or 2, characterized in that: The aminated cellulose is obtained by reacting microcrystalline cellulose with aminopropyltriethoxysilane.

4. The method for preparing the biomass super strong universal adhesive according to claim 1 or 2, characterized in that: The oxidized tannin aqueous solution is obtained by reacting hydrogen peroxide with a tannin aqueous solution.

5. The method for preparing the biomass super strong universal adhesive according to claim 1 or 2, characterized in that: The solid content of the oxidized tannin aqueous solution is 20-40%.

6. The biomass super strong universal adhesive prepared by the preparation method according to any one of claims 1 to 5.

7. The method for using the biomass super strong universal adhesive according to claim 6, characterized in that: The following steps are involved: The biomass super-strong universal adhesive is used to overlap different substrates, and the bonding of the different substrates is completed through room temperature curing or heating curing.

8. The method for using the biomass super strong universal adhesive according to claim 7, characterized in that: The room temperature curing time is 72 to 240 hours.

9. The method for using the biomass super strong universal adhesive according to claim 7, characterized in that: The temperature of the heating curing is 60-120° C., and the time is 0.5-1 hour.

10. The method for using the biomass super strong universal adhesive according to claim 7, characterized in that: The substrate includes one or more of wood, bamboo, stainless steel, aluminum, iron, copper, glass, marble, artificial quartz stone, zirconium oxide, and cloth.

Citation Information

Patent Citations

  • Amine-functionalized modified cellulose cross-linked network structure as well as preparation method and application thereof

    CN114836149A

  • Tannic acid-based wood adhesive and preparation method thereof

    CN118360008A

  • Full-biomass-based environment-friendly underwater adhesive and preparation method thereof

    CN119039914A

  • Water-based adhesive composition and wood panel using the same

    JP2004231814A

  • Adhesive compositions made from plant protein and phenolics

    US20200032121A1